Disruptive approach to integrate data in a digital environment: progress report CIMMYT-Bluenumber 2023 - Gardeazabal Monsalve, Andrea; Gonzalez Naranjo, Daniel (CGIAR, 2023)
This report describes the process carried out a pilot project to evaluate a scalable disruptive approach to integrating data for agronomy research that also incentivizes sustainable production and enables traceability using open data sharing protocol with self-sovereign identity (SSI).